Feasibility of the International Caries Classification and Management System (ICCMS) Protocol in a Hospital-Based Setting in India - Imam Azam; Vijay P. Mathur; Nitesh Tewari; Rahul Morankar; Kalpana Bansal; Anju Rajwar (Indian Journal of Dental Research)
Objective: To evaluate the feasibility of the International Caries Classification and Management System (ICCMS) protocol in a hospital-based setting in India. Methods: A total of 160 children, 3–6 years old children reporting with dental caries to a hospital-based setting were recruited. Risk-based management of dental caries was conducted and followed for one year as per the modified ICCMS protocol. The feasibility of the ICCMS protocol was evaluated based on treatment outcomes including symptom reduction, patient compliance, and time taken in risk assessment. Qualitative outcomes were assessed using a paired t-test, whereas the Wilcoxon signed-rank test assessed the change in quantitative variables from baseline to one year. Results: A one-year follow-up assessment was completed for 139 children. Majority of children (101 = 72.7%) had high caries risk, while (38 = 27.3%) had moderate risk. A significant improvement was observed in terms of reduction in patient symptoms such as reducing the number of active caries, maintaining sound teeth, and maintaining restored teeth (P < 0.05). The time taken for risk assessment was also significantly reduced (mean difference 1.99 ± 3.37 min) at one-year recall. Conclusion: The ICCMS protocol for caries management is feasible in terms of systematic symptom reduction in both moderate and high dental caries risk patients.